2015
DOI: 10.1016/j.juro.2014.10.118
|View full text |Cite
|
Sign up to set email alerts
|

Categorization of Bladder Dynamics and Treatment after Fetal Myelomeningocele Repair: First 50 Cases Prospectively Assessed

Abstract: Of patients who underwent myelomeningocele closure during gestation 93.7% had significant lower urinary tract dysfunction consisting of high bladder pressure or incontinence. These data reinforce the absolute need to follow these patients closely. The potential benefits of fetal surgery in the urinary tract remain to be proved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 12 publications
1
31
1
1
Order By: Relevance
“…In a first report including 19 patients after prenatal MMC closure, they showed abnormal lower urinary tract function in all patients at a follow‐up of 5.4 months, with hyperactive bladder in 90% and upper tract dilatation in 37% of patients . In a second publication, they showed in a cohort of 51 patients that 94% of patients who underwent prenatal MMC closure displayed significant lower urinary tract dysfunction . Interestingly, the first publication to report a positive effect of prenatal repair on the urological outcome was from Carr et al (Philadelphia, USA) who presented their 5‐year urological follow‐up in the pre‐MOMS cohort focusing on continence .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a first report including 19 patients after prenatal MMC closure, they showed abnormal lower urinary tract function in all patients at a follow‐up of 5.4 months, with hyperactive bladder in 90% and upper tract dilatation in 37% of patients . In a second publication, they showed in a cohort of 51 patients that 94% of patients who underwent prenatal MMC closure displayed significant lower urinary tract dysfunction . Interestingly, the first publication to report a positive effect of prenatal repair on the urological outcome was from Carr et al (Philadelphia, USA) who presented their 5‐year urological follow‐up in the pre‐MOMS cohort focusing on continence .…”
Section: Discussionmentioning
confidence: 99%
“…This milestone publication did not address urological outcomes; therefore, little is known about the effect of prenatal MMC closure on the neurogenic bladder dysfunction. There are only a few, mainly retrospective studies, focusing on urinary tract outcomes of prenatal MMC repair . Most of these studies did not demonstrate a positive effect of prenatal MMC repair on lower urinary tract function.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [43] conducted a retrospective study to compare lower urinary tract function between the pre and postnatal MM repair groups and did not find differences between the two. Leal da Cruz et al [44] analyzed our cohort of the first 51 patients and found that 93.7% had significantly less urinary tract dysfunction of high bladder pressure or incontinence. These results reveal the challenges that still have to be overcome in patients with MM.…”
Section: Postoperative Carementioning
confidence: 99%
“…11 Another prospective study failed to show any benefit on the urinary tract, with over 90% of patients demonstrating urinary tract dysfunction on urodynamics in the first year. 12 Prenatal intervention should currently be considered only in the context of clinical trials in specialized centres, where the expertise exists to minimize the risks to mother and fetus.…”
Section: Peter D Metcalfe Md Mscmentioning
confidence: 99%
“…11,27 Most perforations occur in the posterior aspect of the bladder-bowel anastomosis and, therefore, identification and repair may require bivalving the bladder completely. 12,31 Worse still is that due to the neurogenic situation, the initial injury may go unnoticed and result in a late presentation. Therefore, a high index of suspicion is required once a patient has had an augmentation.…”
Section: Elementary Schoolmentioning
confidence: 99%